Voice-Leading Considerations In Edo-Period Jiuta-Tegotomono: A New Analytical Approach - Burnett, Henry (Analytical Approaches to World Music, 2011)
This article seeks to clarify the modal voice-leading structure of Japanese Edo-period chamber music (roughly the music composed in both the kansai and kanto areas from 1690 to 1868), in particular that of shamisen jiuta tegotomono. In doing so, a new theory of modal organization is presented through detailed analyses of several important works within the genre, using Ishikawa Kōtō’s seminal piece Aoyagi as a case study. In addition, the article presents a detailed discussion of the voice-leading properties inherent in the in-senpō mode that governs virtually all Edo-period chamber music for shamisen, koto and shakuhachi, the so-called sankyoku ensemble, and which, up till now, has been little understood by both Japanese and Western scholars. In particular, the in mode is perceived in this new theory as a hexachord divided into two symmetrically related trichords that articulate a fifth relationship that operates as the background structure of the composition. Each trichord within the larger hexachord is then capable of being transposed in either a dominant or subdominant direction, thus expanding the tonal ambitus of the composition, creating new tonal centers and adding new chromatic pitch classes in the process. Lastly, the article illustrates how this music can be graphed, based on an understanding of the pitch relationships that inform the component trichords of the in-senpō mode. In so doing, all the pitch relationships within the composition can now be better understood as to their particular voice-leading functions giving us a clearer understanding of how this cultivated art music operates on a compositional level.